Laboratory radiative accretion shocks on GEKKO XII laser facility for POLAR project. (19th June 2018) - Van Box Som, L.; Falize, É.; Koenig, M.; Sakawa, Y.; Albertazzi, B.; Barroso, P.; Bonnet-Bidaud, J.-M.; Busschaert, C.; Ciardi, A.; Hara, Y.; Katsuki, N.; Kumar, R.; et al.
Abstract : A new target design is presented to model high-energy radiative accretion shocks in polars. In this paper, we present the experimental results obtained on the GEKKO XII laser facility for the POLAR project. The experimental results are compared with 2D FCI2 simulations to characterize the dynamics and the structure of plasma flow before and after the collision. The good agreement between simulations and experimental data confirms the formation of a reverse shock where cooling losses start modifying the post-shock region. With the multi-material structure of the target, a hydrodynamic collimation is exhibited and a radiative structure coupled with the reverse shock is highlighted in both experimental data and simulations. The flexibility of the laser energy produced on GEKKO XII allowed us to produce high-velocity flows and study new and interesting radiation hydrodynamic regimes between those obtained on the LULI2000 and Orion laser facilities.